2018
DOI: 10.3390/geosciences8060203
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soils and Soil Ecosystems to the Pennsylvanian–Permian Climate Transition in the Upper Fluvial Plain of the Dunkard Basin, Southeastern Ohio, USA

Abstract: Direct exposure of paleosols to the atmosphere during formation make them ideal for reconstructing paleoclimate. Paleosol and ichnofossil properties are dependently linked making it important to study them in tandem, to avoid errors in interpretation. Small scale studies (<1 km) yield high resolution data that can be used to assess allogenic processes through comparison of spatial and temporal trends. This study used field and laboratory analyses to gather data from Late Pennsylvanian to Early Permian Upper Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(201 reference statements)
2
2
0
Order By: Relevance
“…A transition to a more stable, seasonally dry environment then occurred through the rest of the Monongahela Group followed by seasonally wet conditions at the base to middle of the Lower Dunkard Group, with small scale fluctuations in between, before a switch to seasonally dry conditions at the top. These climatic trends generally agreed with local studies on correlative strata conducted by Hembree and Bowen (2017) and Hembree and Carnes (2018).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A transition to a more stable, seasonally dry environment then occurred through the rest of the Monongahela Group followed by seasonally wet conditions at the base to middle of the Lower Dunkard Group, with small scale fluctuations in between, before a switch to seasonally dry conditions at the top. These climatic trends generally agreed with local studies on correlative strata conducted by Hembree and Bowen (2017) and Hembree and Carnes (2018).…”
Section: Resultssupporting
confidence: 89%
“…Hembree and Bowen's (2017) study of Upper Monongahela and Lower Dunkard group paleosols yielded an upward trend of decreasing mean annual precipitation (MAP) and increasing seasonality. This same transition was recognized by Hembree and Carnes (2018) in three Upper Monongahela and Lower Dunkard group outcrops. A third study conducted by Hembree and Blair (2016) on outcrops of the Washington Formation revealed thick, repeating successions of calcareous Vertisols characteristic of dry and seasonal conditions.…”
Section: Late Pennsylvanian To Early Permian Paleosolssupporting
confidence: 73%
See 2 more Smart Citations